ОБЩАЯ ХАРАКТЕРИСТИКА СИСТЕМЫ «ОБРАЗОВАНИЕ - НАУКА - ПРОИЗВОДСТВО» - G. Zh. Tayauova; G. Zh. Alibekova; Zh. B. Ilmaliyev; O. B. Kenzhaliyev (Экономика: стратегия и практика)
This article is devoted to the description of the general characteristics of the elements of the system such as education, science and production. The paper presents statistical data on indicators of the state and development of science in the Republic of Kazakhstan over the past 5 years, examines the experience of foreign countries in financing R & D, as well as the innovative activity of enterprises in Kazakhstan. The results of the study show that education, science and production need to create effective programs and mechanisms to support their interaction, improve the level of the manufacturing industry, and develop an entrepreneurial ecosystem.